Round Table as a Beginning: Questions, Debates, and Provisional Conclusions. (2018) - Miller, Alice M.; Engle, Karen; Brown, Widney; Ahmed, Aziza; Gumieri, Sinara; Eisert, Carrie
Abstract : Audience members asked questions regarding specific practices and in particular circled around the question of other ways forward—what other practices should be used to hold actors accountable for violence, especially the often still locally neglected problem of violence against women, as well as violence against people with diverse or stigmatized gender and sexual expressions and identities.